PENGARUH PARENTAL STYLE DAN PENDAPATAN KELUARGA TERHADAP KETERLIBATAN ANAK DALAM KEPUTUSAN PEMBELIAN KELUARGA - Miftahuddin, Muhammad Agung; Purwanto, BM (Faculty of Economics and Business, University of Muhammadiyah Malang, 2010)
The objective of this research is to investigate the effect of parental style and family income on children’s involvement in family purchasing decision. Using dyadic method, the samples of this research consist of 43 parent (fathers or mothers) and 43 children whose ranged 11-16 years old as respondent. The result of this research shows that parental style, with its four dimensions (authoritative, authoritarian, indulgent and neglecting), has no significant difference on children’s involvement in family purchasing decision. Another result in this research shows that family income difference does not influence the children’s involvement level in family purchasing decision. The last, it is also indicated that children using bilateral strategy have a higher signification of influence than those who use unilateral strategy.